Ethical aspects of workplace urine screening for drug abuse. Issue 1 (February 1997) - Forrest, A R
Abstract : OBJECTIVE: To review the ethical and legal implications of the involvement of medical practitioners in workplace screening for drug misuse. CONCLUSIONS: Workplace screening for drugs of abuse raises many ethical issues. If screening is considered as being part of medical practice with the involvement of occupational health physicians, as suggested by the Faculty of Occupational Medicine, then the ethical requirements of a normal medical consultation are fully applicable. The employee's full and informed consent to the process must be obtained and the employee should have an unfettered right of access to all the relevant records and to the urine sample he/she has provided in the event that he/she wishes to challenge the opinion expressed by the physician. If the process is not part of medical practice then employees should have the same rights as they would have if required to provide intimate body samples in the course of a criminal investigation, given the potentially serious consequences of an erroneous positive finding for their livelihood.